Are We Ready to Have Teachers with Learning Disabilities? A Study of School Principals’ Observations - Flavian, Heidi (Journal of the American Academy of Special Education Professionals, 2016)
For decades, lawmakers, parents, and educators have advocated for including students with learning disabilities (LD) and addressing their needs within the education system. However, LD-related challenges do not vanish with age; consequently, for college and university graduates with LD, the issue of inclusion begins again when they reach the job market, including when they want to become teachers. The success of inclusion relies on the society’s readiness to change and to accept people with a variety of difficulties in all areas of life. This study focuses on school principals’ views regarding the hiring of teachers with LD. Apparently, although principals understand the variety of ways students with special needs should be included, they still struggle with the idea of including teachers with LD.